PRODUCING THE “PROBLEM” OF PARENTAL OVERSHARE - Kumar, Priya C. (AoIR Selected Papers of Internet Research, 2021)
With the rise of social media, the term overshare has become shorthand for concerns about people, especially parents, disclosing seemingly excessive amounts of information. Prior work shows that the term overshare does not simply describe an action, but reinforces problematic boundaries that marginalize women. In this paper, I examine how social media discourse actively produces oversharing and then instructs parents to self-censor in the name of satisfying their social media audience. I focus on STFU, Parents, a once-popular blog dedicated to mocking parental overshare. I analyze STFU, Parents materials through the framework of governmentality, a Foucauldian-inspired means of examining how authorities intervene in people’s lives. I find that STFU, Parents defines overshare as the posting of gross or overly emotional content on social media. It materializes overshare through the technologies of screenshots, which supply evidence of overshare, and editing software, which anonymizes the people in the post and enables STFU, Parents to distance itself from the consequences of publishing other people’s information. STFU, Parents portrays itself as simply curating a phenomenon—overshare—that exists in the world. However, I argue that STFU, Parents brings overshare into being by pulling information out of context and using it as a reason to judge parents, particularly mothers. Presenting overshare as a problem of individuals not knowing proper social media etiquette enables STFU, Parents to distance itself from its role role in constructing the very problem it claims to critique.